(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: This study aimed to evaluate the strengths, weaknesses, opportunities, and threats (SWOT) of implementing telehealth intervention in the management of outpatients with type 2 diabetes at Lien Chieu District Medical Center, Da Nang City. Methods: A cross-sectional study was conducted in October 2023 at Lien Chieu District Medical Center. The study included 33 outpatients with type 2 diabetes and 13 healthcare workers working in Department of Internal Medicine and the Department of Public Health and Food Safety. Results: The average age of the study subjects was 46.7 ± 14.2 years, with healthcare workers being younger at 31.1 ± 8.2 years and females comprising the majority (63.0%). Based on a 5-point Likert scale, the patients and healthcare workers rated the strengths, weaknesses, opportunities, and threats at 76.1%, 69.6%, 52.2%, 56.5%. Conlusion: Lien Chieu District Medical Center has more strengths and opportunities than weaknesses, with strong agreement from both patients and healthcare workers, regarding the implementing telehealth intervention in the management of outpatients with type 2 diabetes. Therefore, it is feasible to implement telehealth intervention for patients with type 2 diabetes at Lien Chieu center.